ECONOMICS ANALYSIS OF BAMBOO MARKETING IN ANAMBRA AGRICULTURAL ZONE OF ANAMBRA STATE, NIGERIA - Anarah, Samuel Emeka; Umeukeje, A. Peace; Obiajulu, I. Samuel; Meludu, N. Theresa (FUDMA JOURNAL OF SCIENCES, 2025)
The study examined the economics analysis of bamboo marketing in Anambra Agricultural zone of Anambra State, Nigeria. The study looked at the profitability of bamboo marketing in the study area, ascertain the constraints faced by bamboo marketers and determine the sources of funds, labour and transportation mode in bamboo marketing. Data were collected from 60 respondents, (40 retailers and 20 wholesalers), who were selected purposively from four major markets in Anambra Agricultural zone using snowball sampling method. The four major markets in the zone were Otuocha, Oye-Olisa, Eke-Igwe Nteje and Oye-Farm at Igbariam. Data were analyzed using descriptive statistics, gross margin (GM) and 3 types Likert scale. About 38.6 % of the bamboo marketers in the study area sources fund from co-operative societies, 30% of the marketers sources fund from family members and relatives, 41% of the marketers use their personal bus and truck for transportation of bamboo to either shop or place of request. Majority of respondents were found to utilize hired labour (36.6 %) to harvest bamboo from the forest, 26.6 % use hired and family labour for the harvest. The total revenue generated in bamboo marketing in Anambra Agricultural zone by both wholesalers and retailers are 80,500,300 and 9,674,054 respectively. High cost of bamboo, high cost of transportation, high demand, poor sales, poor storage facility and bad weather are the constraints in bamboo marketing. Bamboo marketers should be encouraged to gain knowledge production through seminars and workshops to increase profit in the area.